Posterior ataxia-paraparesis syndrome in the large-breed dog - POLIZOPOULOU (Ζ. Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; KOUTINAS (X.Κ. ΚΟΥΤΙΝΑΣ), C. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The most common conditions associated with the posterior ataxia-paraparesis syndrome in large breed dogs are degenerative myelopathy, type II intervertebral disk disease, spinal cord neoplasms (extradural, extramedullary, intradural, intramedullary), cervical vertebral malformation-malarticulation, lumbosacral spondylopathy, diskospondylitis and distemper myelitis. These progressive myelopathies, which are often seen in aging dogs, are characterized clinically by posterior ataxia and UMN and/or LMN paraparesis that may result in paraplegia late in the course of the disease. In a certain number of cases the clinical picture is further deteriorated by concomitant hip dysplasia associated with osteoarthritis. Spinal radiography of myelopathic dogs may reveal spondylosis deformans or dural ossification to which their clinical signs could be erroneously attributed. Lesions of the spinal cord are localized and their etiology is determined with the aid of radiography, myelography, CT or MRI, CSF analysis and electrodiagnostic examination (somatosensor evoked potentials, electromyogram). In general, the various therapeutic modalities (decompressive surgeries, medication, exercise, physical therapy, avoidance of the complications associated with prolonged recumbency) usually applied in these cases are also discussed.